"Doing the Best We Can": Providing Care in a Malawian Antiretroviral Clinic. Issue 2 (3rd March 2016) - Rosenthal, Anat
ABSTRACT: Following a national policy shift toward universal access to antiretroviral therapy (ART) in Malawi, hospitals and clinics around the country made major changes to enable the provision of ART. In this already resource-limited environment, the provision of ART brought new health care delivery challenges to bear on both patients and health care professionals. The substance and form of these local interventions are affected by a multilayered global context. Drawing on fieldwork in an antiretroviral clinic in rural Malawi, this article discusses the daily implications of providing and receiving care in the context of a massive global shift in health policy, and argues that in order to fully understand the process of service rollout in all its complexity, care should be explored not only from the patients' perspective but also from that of local and international health care professionals and policymakers.